2011
DOI: 10.1111/j.1475-4932.2010.00704.x
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Competition, Technical Efficiency and Quality

Abstract: This paper studies the link between competition and technical efficiency of public hospitals in the state of Victoria, Australia. It finds a positive relationship between efficiency and competition as measured by the Hirschman–Herfindahl Index (HHI) and a negative relationship when the number of competing private hospitals is used instead of HHI. It also finds that whether or not quality is treated as an endogenous output variable influences the statistical estimates of the link between efficiency and competit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“… 53–55 The other two papers did not study the relationship between competition and hospital quality ( Table 2 ). 56 , 57 …”
Section: Resultsmentioning
confidence: 99%
“… 53–55 The other two papers did not study the relationship between competition and hospital quality ( Table 2 ). 56 , 57 …”
Section: Resultsmentioning
confidence: 99%
“…6,30,31 Bates et al 6 analyzed how market structure, measured by competition among rivals, presence of HMOs, and the buying power of health insurers, affects the level of technical efficiency in the hospital service industry. They did not find evidence that greater rivalry increases technical efficiency.…”
Section: Hospital Competition and Efficiencymentioning
confidence: 99%
“…However, in the market for hospital services, it is unclear whether hospital competition enhances hospital efficiency . Some studies have found that when a hospital was located in a highly competitive market, its efficiency score was higher than the scores of hospitals in a less competitive market . Other studies have reported no evidence that increasing the degree of competition among hospitals increases technical efficiency …”
Section: Theoretical Foundation/conceptual Modelmentioning
confidence: 99%